THE SPECIAL FEATURES OF GEORGIA’S POLITICAL MEDIA MILIEU AFTER THE ROSE REVOLUTION - CHEDIA, Beka (CENTRAL ASIA AND THE CAUCASUS, 2007)
The formation of independent media is one of the main achievements of the many years of reform of the Georgian political system.Georgia’s mass media is developing faster than other civil institutions. Despite the low level of election democracy, local self-government, and political parties, state-independent mass media organizations came into being after Georgia gained its independence. But—unfortunately there has to be a “but”—the mass media in Georgia have not only become the main lever in public opinion formation, but they are also a hefty weapon in the political struggle. Confirmation of this was the so-called Rose Revolution in November 2003, which not only raised the significance of the mass media, particularly television, but also revealed several shortcomings in their work. State-independent television played a very important, if not decisive, role both in forming public moods and in raising the wave of revolutionary protest.1 Until the parliamentary elections of 2003 (which escalated into the revolution), television companies could still deny their politicized nature and claim that they were trying to be objective; however, the revolution revealed and polarized their political views. The Rustavi-2 TV channel openly supported the revolution. Later, one of the popular anchorwomen on this television station admitted that the channel covered all the events of those days extremely tendentiously. So, Rustavi-2 turned out to be closely associated with the victorious political forces. It soon